A port-stream based equation oriented modelling of complex distillation column: A dividing wall column case study - Rosshila, Idris; Noorlisa, Harun; Mohamad Rizza, Othman (EnPress Publisher, LLC, 2020)
Dividing wall column (DWC) offers higher degree of freedom in comparison with the conventional column. Furthermore, the different sections configurations within the column are highly interacting with several recycle loops. Facing with such complex unit operation, describing its behaviour encourages the focal point on the resolution of ideal modelling approaches. Equation oriented (EO) modelling of DWC has been studied by several researchers involving complex algorithm and methodology. In this work, a new approach for modelling of DWC is presented. The modelling methodology involves variables connectivity based on ports and streams that is admissible to equation-oriented flow sheet. To verify the functionality of the proposed method, the modelled DWC is validated with two case studies depicted from experimental literature data to separate alcohol mixture and fatty acid fractionation. The model development was performed in MOSAIC, a web-based modelling tool and run in gPROMS. The model shows good convergence and has less than 10% error when compared to the above mentioned case studies. To furthermore extend the model capability, relative gain array (RGA) analysis was conducted for the fatty acid fractionation to determine the best control configuration in DWC. Result shows that L-S-V and L-S-B configurations are the best control configurations. Our analysis also shows that reflux flowrate, side flowrate and vapor boilup are best to control distillate product, side product and bottom product, respectively.